2003
DOI: 10.1556/aagr.51.2003.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of groundnut (Arachis hypogaea L.) to drought stress and its amelioration: A review

Abstract: Groundnut (Arachis hypogaea L.) is an important cash crop for tropical farmers. It is an annual legume and its seeds contain high amounts of edible oil (43-55%) and protein (25-28%). Even though it is fairly drought-tolerant, production fluctuates considerably as a result of rainfall variability. To develop a water stress response function in groundnut, research has been done to improve the performance under varying degrees of stress at various physiological stages of crop growth. This review summarizes recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
133
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(140 citation statements)
references
References 54 publications
5
133
0
2
Order By: Relevance
“…Terminal drought generally reduced pod weight, seed weight, and harvest index (Nautiyal et al, 1999;Reddy et al, 2003) and resulted in yield reduction and low seed quality. Koolachart et al (2013) showed that terminal drought caused 38%-42% yield reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Terminal drought generally reduced pod weight, seed weight, and harvest index (Nautiyal et al, 1999;Reddy et al, 2003) and resulted in yield reduction and low seed quality. Koolachart et al (2013) showed that terminal drought caused 38%-42% yield reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Since it is mainly grown as a rainfed crop, drought is the most limiting factor, resulting in low yields in many parts of the world (Reddy et al, 2003;Songsri et al, 2008). Frequent failure of rains late in the season has resulted in decreased yield and poor quality peanuts (Kambiranda et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To avoid water loss and evaporation by expanded leaf area, plants decrease individual leaf area, total leaf area per plant and the number of leaves per plant. Eventually, reduction of leaf area by drought decreases plants' growth and photosynthesis (Reddy et al, 2003;Shao et al, 2008).…”
Section: Morphological Physiological and Biochemical Responses Undermentioning
confidence: 99%
“…Many production areas are in semiarid environments or have unreliable rainfall, and global climate changes and growing demand for fresh water pose major challenges. Physiological adaptation and selection for drought tolerance have been studied by many researchers (Reddy et al, 2003). Study of peanut genomics has been limited by biological constraints, and many basic tools of genomics have yet to be developed (Gepts et al, 2005).…”
Section: Gene Expression During Drought Stress In Peanutsmentioning
confidence: 99%
“…Peanut is grown on 35.5 million ha across 82 countries in the world. More than half of the production area, which accounts for 70% of the peanut growing area fall under arid and semi-arid regions, where peanuts are frequently subjected to drought stresses for different duration and intensities (Reddy et al, 2003). An annual estimated loss in peanut production equivalent to over US$520 million is caused by dro ught.…”
Section: Introductionmentioning
confidence: 99%